PENINGKATAN KUALITAS PEMBELAJARAN IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBASIS LINGKUNGAN (Joyful Learning Journal, 2012)
Tujuan penelitian ini adalah mendeskripsikan aktivitas guru, aktivitas siswa dan meningkatkan keterampilan hasil belajar siswa pada pembelajaran IPA melalui melalui Model PembelajaranKooperatif tipe Group Investigation Berbasis Lingkungan.Hasil penelitian menunjukkan bahwa Model Pembelajaran Kooperatif tipe Group Investigation Berbasis Lingkungan dapat meningkatkan kualitas pembelajaran IPA. Keterampilan guru siklus I dengan persentase 58,3% dalam kategori cukup, siklus II dengan persentase 80,6% dalam kategori baik, dan siklus III dengan persentase 88,9% dalam kategori sangat baik. Aktivitas siswa siklus I dengan rata-rata skor 23,3 dalam kategori baik, siklus II dengan rata-rata skor 28,5 dalam kategori baik, dan siklus III dengan rata-rata skor 30,1 dalam kategori sangat baik. Ketuntasan klasikal hasil belajar siswa siklus I dengan persentase 65,9% dalam kategori cukup, siklus II dengan persentase 72,7% dalam kategori baik, dan siklus III dengan persentase 86,4% dengan kategori sangat baik. Berdasarkan analisis hasil penelitian tindakan kelas tersebut disimpulkan, bahwa pembelajaran IPA melalui Model Pembelajaran Kooperatif tipe Group Investigation Berbasis Lingkungan dapat meningkatkan keterampilan guru, aktivitas siswa dan hasil belajar siswaThe purpose of this study is to describe the activity of the teacher, student activities and improve students' skills in learning science through the through type Group Investigation Approach Based Cooperative Environment.The design of this study was a class act with the stages of research planning, implementation of the action, observation and reflection. This study consisted of three cycles each cycle two meetings one session in three cycles. The subject of this study were teachers and 44 fourth grade students of SDN Karanganyar 01. Data collection techniques using the method of observation, field notes, test methods, methods of documentation, and interview methods.The results show the type of Group Investigation Approach Based Cooperative Environment to improve the quality of science learning. I cycle skills with the percentage of teachers 58,.3% in the category enough, the second cycle with the percentage of 80,6% in both categories, and the percentage of cycle III with 88,9% in the excellent category. I cycle the student activity with an average score of 23,3 in both categories, the second cycle with an average score of 28.5 in both categories, and the cycle III with an average score of  30,1 in the excellent category. Classical completeness of student learning outcomes I cycle with the percentage of 65,9% in the category enough, the second cycle with the percentage of 72,7% in both categories, and the third cycle with the percentage of 86,4% with very good category.Based on the analysis results can be concluded that class action, that learning science through Cooperative Approach Type-Based Environmental Investigation Group can improve teachers' skills, student activities and learning outcomes in each learning siswa.